OPPORTUNITY OF IMPROVING THE SPEED QUALITY OF KIDS UP TO 11 YEARS AGE, PRACTICING FOOTBALL - Y. Gorelski (Trakia Journal of Sciences)
Changes in speed, length and frequency of the running stride have been taken into account with and without a ball in a football game. Differences have been observed in its structure in linear acceleration and in a game of “square“,which requires а special preparation,enhancing and automating of two biomechanical indicators of speed and increasing the efficiency in a football game.